LncRNA MIAT promotes esophageal squamous cell carcinoma progression by regulating miR‐1301‐3p/INCENP axis and interacting with SOX2. Issue 11 (14th January 2020) - Zhang, Chunyan; Xie, Linsen; Fu, Yin; Yang, Juanjuan; Cui, Yuanbo
Abstract: Long noncoding RNAs (lncRNAs) have been reported to participate in the development of multiple cancers, including esophageal squamous cell carcinoma (ESCC). A growing number of studies have demonstrated that lncRNA myocardial infarction‐associated transcript (MIAT) played an oncogenic role in several human malignancies, but its expression and function in ESCC remain unknown. In this study, we found that MIAT was significantly increased in ESCC tissues, as well as cell lines. Downregulation of MIAT suppressed ESCC cell proliferation, cell cycle, migration, and invasion. Mechanical studies revealed that MIAT promoted ESCC cell proliferation and cell cycle by acting as a competitively endogenous RNA (ceRNA) to upregulate the inner centromere protein (INCENP) expression through sponging miR‐1301‐3p. Furthermore, we uncovered that MIAT‐SOX2 formed a positive feedback loop to facilitate cell proliferation, migration, and invasion of ESCC. Our findings indicated that MIAT promoted ESCC progression via targeting INCENP/miR‐1301‐3p axis and interacting with SOX2, suggesting novel potential therapeutic targets for ESCC. Abstract : 1. LncRNA MIAT is highly expressed in ESCC tissues and cell lines and knockdown of MIAT inhibits ESCC proliferation both in vitro and in vivo. 2. MIAT promotes ESCC proliferation partially by functioning as a ceRNA to upregulate INCENP expression via sponging miR‐1301‐3p. 3. MIAT‐SOX2 forms a positive feedback loop to promote ESCC proliferation and metastasis.